Open-source development experiences in scientific software: the HANDE quantum Monte Carlo project - Spencer,JS; Blunt,NS; Vigor,WA; Malone,FD; Foulkes,WMC; Shepherd,JJ; Thom,AJW (Journal of Open Research Software, 2015)
The HANDE quantum Monte Carlo project offers accessible stochastic algorithmsfor general use for scientists in the field of quantum chemistry. HANDE is anambitious and general high-performance code developed by ageographically-dispersed team with a variety of backgrounds in computationalscience. In the course of preparing a public, open-source release, we havetaken this opportunity to step back and look at what we have done and what wehope to do in the future. We pay particular attention to development processes,the approach taken to train students joining the project, and how a flathierarchical structure aids communication